Seven for a secret - Astley, Judy, author 543128 (London : Transworld Publishers Limited, 1996)
It was Heather's silver wedding anniversary. But this important milestone did not mark her marriage to Tom, her often-absent airline pilot husband and father of their two teenage children. It was for her first marriage - a wildly romantic, secret affair, when she and Iain - twelve years older than her and the heir to a Scottish baronetcy - had eloped immediately after her final school speech day. She was just sixteen at the time. The marriage had not lasted twenty-five weeks, let alone years, and it was, as her mother firmly announced, As If It Never Happened. But secrets have a habit of coming out, and when a film crew arrived in the attractive Thamesside village where Heather and Tom lived, Heather was horrified to find her ex-husband amongst them. As Heather and Iain met again, many secrets jostled to be revealed, including Tom's own highly secret life. Heather, her daughter Kate - the same age as Heather was when she embarked upon her disastrous elopement - and her mother Delia all had to reveal things which they never thought would need to be revealed, and their peaceful Oxfordshire village community buzzed with speculation and scandal.